2007
DOI: 10.1002/marc.200600747
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Aqueous Polyimidization Using High‐Throughput Techniques

Abstract: High‐throughput methodology, as used in pharmaceutical drug discovery, was successfully applied to high performance polyimide development. Using a Biotage® microwave reactor fitted with a flask handling robot and a high‐throughput approach, we have optimized a copolyimide material with high Tg, yet maintaining solution processability. Additionally, the development time for this material has been reduced from months to just weeks. The polyimide was produced using combinations of the monomers 4,4′‐ODA, 6‐FDA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…obtained amorphous PIs most likely due to the highly flexible monomers they employed, and Dao et al . synthesized statistical co‐polyimides that were also amorphous . By shortening t h down to 2 min in the present study, we obtained higher crystallinity for both P1 and P2 than previously reported .…”
Section: Introductionsupporting
confidence: 43%
See 2 more Smart Citations
“…obtained amorphous PIs most likely due to the highly flexible monomers they employed, and Dao et al . synthesized statistical co‐polyimides that were also amorphous . By shortening t h down to 2 min in the present study, we obtained higher crystallinity for both P1 and P2 than previously reported .…”
Section: Introductionsupporting
confidence: 43%
“…In this study, we use a microwave reactor enabling control over the heating time, t h . Microwave‐assisted PI syntheses in water have been previously reported, the final PIs were however noncrystalline: Brunel et al . obtained amorphous PIs most likely due to the highly flexible monomers they employed, and Dao et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groth and coworkers prepared co-polyimides of different composition from 4,4 -oxidianiline and benzene-1,2,4,5-tetracarboxylic acid/4,4 -(hexafluoroisopropylidene)diphthalic acid mixtures in a monomode MW reactor equipped with an auto-sampler. [92] After optimization, conditions of 45 min of MW irradiation at 190 • C with a monomer ratio of 2:1:1 yielded a polymer with a molecular weight of 31 500 g mol −1 and a glass transition temperature of 347 • C. The authors emphasized the potential of time reduction by using an automated MW technique, which facilitated the development of a polyimide material with high thermal and mechanical stability within weeks instead of months.…”
Section: Polyimidesmentioning
confidence: 97%
“…The use of microwave energy for the obtention of polyimides39 has had great acceptance, for the synthesis of poly(piromellitidimides) by means of monomers of nylon‐salt‐type 40, 41. Polyimides of aromatics dianhydrides and diisocyanates were prepared,42 reducing the polymerization reaction times,41 with regard to the same polymers obtained by means of conductive heating.…”
Section: Introductionmentioning
confidence: 99%